Emotional embeddedness: a process of becoming a small business owner. (2016) - Murthy, Venkatesh; Paul, Bino
This study examines the circumstances that prompt individuals to become small business owners. Using qualitative research, grounded theory approach, and with the help of narratives, this study builds on Elster's (1998) characteristics of emotions, namely, cognitive antecedents, intentional objects, physiological arousals, valence, and action tendencies. The findings of this study suggest that an individual becomes a small business owner because of the various emotional experiences in his/her childhood caused by interaction with family members.